Possible acute rejection associated with the use of the new antihepatitis C virus medications - Karkout, Khaled Ar; Al Sherif, Saleema; Hussein, Qutaiba; Albawardi, Alia; Boobes, Yousef (Avicenna Journal of Medicine, 2019)
Hepatitis C virus infection is associated with increased morbidity and mortality. It remains a major challenge for management and treatment, especially in patients with renal transplant. The new directacting antiviral agents gave big hopes to both clinicians and patients that they can overcome this challenge without major side effects. Studies recently have supported this claim; however, they are still few, limited, and may give false hopes. In the following case report, we present a case, supported by histological evidence about a possible acute rejection of kidney transplant after treatment with these new medications. This case is limited by the absence of donorspecific antibodies. This report is aimed to increase awareness about the urgent need for further studies.
Keywords: Acute rejection; anti-hepatitis C virus medication; daclatasvir; direct-acting antiviral agents; kidney transplant; sofosbuvir